2017
DOI: 10.1039/c7ra04059h
|View full text |Cite
|
Sign up to set email alerts
|

EGF-targeting lipodisks for specific delivery of poorly water-soluble anticancer agents to tumour cells

Abstract: Concerns regarding poor aqueous solubility, high toxicity and lack of specificity impede the translation of many hydrophobic anticancer agents into safe and effective anticancer drugs. The application of colloidal drug delivery systems, and in particular the use of lipid-based nanocarriers, has been identified as a promising means to overcome these issues. PEG-stabilized lipid nanodisks (lipodisks) have lately emerged as a novel type of biocompatible, nontoxic and adaptable drug nanocarrier. In this study we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…All lipodisks used in the study were produced with a method based on detergent depletion using Bio-Beads (SM-2 Adsorbent, Bio-rad, Sundbyberg, Sweden) in accordance with a previously described protocol [15,19]. Briefly, for lipodisks used in QCM-D assays a lipid film composed of DSPC:DSPE-PEG2000:DSPE-PEG2000-biotin 80:16:4 was prepared as described above.…”
Section: Production Of Lipodisks and Liposomesmentioning
confidence: 99%
See 2 more Smart Citations
“…All lipodisks used in the study were produced with a method based on detergent depletion using Bio-Beads (SM-2 Adsorbent, Bio-rad, Sundbyberg, Sweden) in accordance with a previously described protocol [15,19]. Briefly, for lipodisks used in QCM-D assays a lipid film composed of DSPC:DSPE-PEG2000:DSPE-PEG2000-biotin 80:16:4 was prepared as described above.…”
Section: Production Of Lipodisks and Liposomesmentioning
confidence: 99%
“…Lipid bilayer disks (lipodisks) are nanosized bilayer structures, stabilized into flat, circular shapes by polyethylene glycol (PEG)-linked lipids [12][13][14]. These nanoparticles show great potential as drug carriers and have been preclinically assessed for delivery of anti-cancer and anti-bacterial compounds [13,[15][16][17][18][19]. Moreover, a targeting moiety can be attached to the lipodisk to increase delivery to desired tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that a formulation in lipodisks can be used as a viable means to increase tumor accumulation and reduce off-target toxicity of both the anticancer peptide melittin and chemotherapeutic drugs, such as doxorubicin and paclitaxel [ 149 ]. Recent results from the Edwards lab showed that by decorating the lipodisks with ligands that recognize selected cell membrane receptors, it is possible to design systems capable of specific tumor cell targeting and true intracellular delivery of both conventional and peptide-based anticancer drugs [ 150 , 151 , 152 ]. In this project by Edwards, the possibilities to use lipodisks for the co-delivery of chemotherapeutic drugs and membranolytic anticancer peptides will be investigated.…”
Section: Phospholipids In Research—project Overviewmentioning
confidence: 99%
“…Several formulation approaches were adapted to improve the EE, including altering drug to lipid (D/L) ratio (23,32), leveraging remote loading (33,34), and increasing polyethylene glycol (PEG) ratios, which promotes the morphology change from liposomes to lipodisks. Lipodisks consist of a disk-like structure where the phospholipids form a flat lipid surface, and the PEG-lipids are located at the highly curved rim (35)(36)(37). Many published results suggest that lipodisks are promising nanocarriers, and the rich contents of PEG may promote improved EE (38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%